The Perceived Applicability of Coaching Skills among Human Resource Business Partners of South African State-Owned Entities - Thato Mmaditla; Elona N. Ndlovu-Hlatshwayo (Journal of Management and Entrepreneurship Research, 2022)
Objective: HRBPs working in the State-owned entity (SOE) industry face a few challenges that inhibit them from being true partners to senior management teams. This research concentrated on whether coaching skills could be included in the Human Resource Business Partner (HRBP) competency model and assist HRBPS in their engagement with senior managers. Research Design & Methods: A qualitative research design was selected to gain insights from the perspectives of HRBPs employed in SOEs in Gauteng, South Africa. All participants had over two years of relevant HRBP experience and participated in a semi-structured interview to solicit their perspectives. The data was consequently analysed using thematic analysis. Findings: The key findings are that the SOE industry is complex to navigate due to the high levels of red tape and capacity constraints. The benefits of coaching, which include enhanced levels of organisational performance and leadership self-awareness, will be achieved in the engagement between HRBPs and senior managers. Furthermore, additional training of all HRBPs on the proposed coaching skills was supported as it was found to be a probable solution to re-position HRBPs as strategic business partners. Contribution & Value Added: This paper positions coaching as a central skill for HRBPs, specifically in the SOE environment in South Africa, by combining two leading competency frameworks, the Ulrich and GSAEC competency frameworks. Although HR is an established field, coaching is relatively emerging with limited frameworks for the profession. This paper addresses the need for guiding frameworks where the two professions intersect.